Bacterial Production and Growth Rate Estimation from [(3)H]Thymidine Incorporation for Attached and Free-Living Bacteria in Aquatic Systems - Iriberri, Juan (1990)
Production and specific growth rates of attached and free-living bacteria were estimated in an oligotrophic marine system, La Salvaje Beach, Vizcaya, Spain, and in a freshwater system having a higher nutrient concentration, Butron River, Vizcaya, Spain. Production was calculated from [methyl-(3)H]thymidine incorporation by estimating specific conversion factors (cells or micrograms of C produced per mole of thymidine incorporated) for attached and free-living bacteria, respectively, in each system. Conversion factors were not statistically different between attached and free-living bacteria: 6.812 × 10(11) and 8.678 × 10(11) μg of C mol(−1) for free-living and attached bacteria in the freshwater system, and 1.276 × 10(11) and 1.354 × 10(11) μg of C mol(−1) for free-living and attached bacteria in the marine system. Therefore, use of a unique conversion factor for the mixed bacterial population is well founded. However, conversion factors were higher in the freshwater system than in the marine system. This could be due to the different trophic conditions of the two systems. Free-living bacteria contributed the most to production in the two systems (85% in the marine system and 67% in the freshwater system) because of their greater contribution to total biomass. Specific growth rates calculated from production data and biomass data were similar for attached and free-living bacteria.